The Role of Destructive Mechanisms within Economic Evolution - Lipieta, Agnieszka; Lipieta, Artur (Panoeconomicus, 2022)
This research is inspired by Joseph Schumpeter’s understanding of economic evolution. In his view, innovations promote economic development, whereas imitations promote the diffusion of innovations, leading the economy through a process that he defines as "creative destruction." A host of economists tend to agree on the importance and consequences of innovations and imitations within economic processes; however, opinions regarding creative destruction tend to differ. One view purports that creative destruction serves as a main variable, pushing the capitalist economic system toward equilibrium through imitation processes. A contrary view suggests that an equilibrium state actually promotes economic growth. Within this context, our research aims to model some mechanisms that may appear within economic evolution. Hurwicz’s concept of economic mechanisms is introduced in a modified ArrowDebreu model, as a way of examining Schumpeter’s ideas on the role of creative destruction in economic processes that does not decrease the positions of agents. In relation to this, the present work suggests that it is indeed possible to design a mechanism that would transform the economic system under consideration toward a state of equilibrium, without making the positions of any agents worse off. JEL: D41, L20, O12.